Perancangan dan Implementasi API PHP pada Sistem Autentifikasi Jaringan SMA N 7 Bengkulu Selatan - Rahman, Riski; Khairil, Khairil; Sudarsono, Aji (MEANS (Media Informasi Analisa dan Sistem), 2023)
One system to be able to access the network can use an authentication system by utilizing the PHP API. In running the authentication system by utilizing the PHP API it is supported by several other tools or applications such as Apache2, PHP and MySQL. So using an authentication system using the PHP API can make settings or user management better such as speed settings, length of access time and other settings. Linux ubuntu server 20.04 is an open source operating system, this operating system is very good for use as a server because it does not require high hardware specifications and can also be obtained free of charge because it is open source. The authentication system is very well implemented at SMA N 7 Bengkulu Selatan, this is because SMA N 7 Begkulu Selatan already has and uses internet access and with an authentication system using the PHP API this can make network management better. Both in terms of user settings, time and speed. In authenticating using the authentication system with the PHP API, it does not require a long time to authenticate, which is less than 5 seconds, this time will also be affected by the conditions of the computer network and the devices used.